ANALISIS YURIDIS HIBAH YANG DIPERHITUNGKAN SEBAGAI WARISAN DARI ORANG TUA KEPADA ANAK MENURUT KOMPILASI HUKUM ISLAM BERDASARKAN PUTUSAN MAHKAMAH AGUNG REPUBLIK INDONESIA NOMOR 10 PK/AG/2006 - TRIYANA RATIH (PREMISE LAW JURNAL, 2017)
One of the methods of preventing from the incidence of dispute in distributing inheritance is by giving it by the parents to thei children while they are still alive. In this case, some people give all of their property to only one of their children and ignore the other children’s right. It, of course, violates against the inheritance law stipulated in KHI (Compilation of the Islamic Laws). The result of the research shows that the regulation on hibah which is regarded as inheritance is stipulated in Article 211 of the KHI. When parents grant their property to all or one third (1/3) of their children, they must get agreement or approval from the other heirs. According to Compilation of the Islamic Laws, if one or more heirs complain about the distribution of inheritance or feel harm, negotiation has to be carried out among them or they can bring the case to the Religious Court to revoke the hibah or distributed it according to Compilation of the Islamic Laws. The review of the Supreme Court’s Ruling No. 10 PK/AG/2006 revokes the judge’s consideration in the Highest Appellate Court which states that the hibah is valid as ampikale is correct and the property is distributed to the other heirs according to their own shares.Keywords: Hibah, Inheritance, Compilation of the Islamic Law